2002
DOI: 10.1177/097185240200600105
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technologies: A Priority for Women

Abstract: The majority of women still do not have access to information and communication technologies (ICTs) which are appropriate to their needs, and neither are they active participants in the process of science and technology development. Women's effective access to information and communication technologies can help them achieve increased participation in production and productivity thereby contribute more to economic development. This article looks at the current situation of women and the digital divide. How can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 1 publication
2
20
0
1
Order By: Relevance
“…Moreover, ICTs help in creating women's leadership, and participation in community and economic development (Anitha & Sundharavadivel, 2012). Most previous research, based mainly on national case studies, has indicated that ICTs increase employability and thus women's empowerment can be advanced (Arun & Arun, 2002;Hafkin & Taggart, 2001;Huyer & Carr, 2002;Islam, 2015;Kelkar & Nathan, 2002;Njelekela & Sanga, 2015;Shirazi, 2012;Suhaida et al, 2013;Umrani & Ghadially, 2003;Wamala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ICTs help in creating women's leadership, and participation in community and economic development (Anitha & Sundharavadivel, 2012). Most previous research, based mainly on national case studies, has indicated that ICTs increase employability and thus women's empowerment can be advanced (Arun & Arun, 2002;Hafkin & Taggart, 2001;Huyer & Carr, 2002;Islam, 2015;Kelkar & Nathan, 2002;Njelekela & Sanga, 2015;Shirazi, 2012;Suhaida et al, 2013;Umrani & Ghadially, 2003;Wamala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Issues related to women's access to and participation In the Internet and other Information and communication technology must he an Integral part o f the strategy. ICT must become a priority for women's political and social action agenda (Harcourt, 2002;Huyer & Carr, 2002;Ines, Munevar, & Arrleta, 2002). A strategy for action must link ICT-related activities, such as building a women's health network, to the goal o f ensuring that all women have the opportunity for access to and participation In ICT and Internet.…”
Section: Women and Information And Communication Technologymentioning
confidence: 99%
“…Women have less access to the technology, skills and knowledge required to use ICT (Huyer & Carr, 2002). Women have limited resources necessary to support the use o f the internet including economic resources, adequate time to learn skills and then to use them, equal share o f computer time in the home and appropriate technical support (Pollock & Sutton, 2003).…”
Section: Digital Divide(s)mentioning
confidence: 99%
See 2 more Smart Citations